Schumpeter Lecture 2019: Slow Household Deleveraging. Issue 6 (27th November 2020) - Guerrieri, Veronica; Lorenzoni, Guido; Prato, Marta
Abstract: We use a model of precautionary savings with housing and mortgages to study the effects of a deleveraging shock on consumer spending. We focus on the deleveraging caused by a contraction in home values, and compute numerically the partial-equilibrium effect of the shock. Our simulations show that household deleveraging is associated with a long and protracted weakness in consumption. These effects appear even if we assume, realistically, that housing wealth is illiquid and mortgage debt is long term. We show that housing wealth matters for consumption decisions due to an insurance force: consumers know they can sell their house if they get hit by sufficiently negative shocks in the future. We also show that our slow deleveraging mechanism is amplified when incomes are affected by a weak aggregate consumption demand through general-equilibrium effects.